2017
DOI: 10.7554/elife.28231.020
|View full text |Cite
|
Sign up to set email alerts
|

Author response: E3 ubiquitin ligase Bre1 couples sister chromatid cohesion establishment to DNA replication in Saccharomyces cerevisiae

Abstract: Bre1, a conserved E3 ubiquitin ligase in Saccharomyces cerevisiae, together with its interacting partner Lge1, are responsible for histone H2B monoubiquitination, which regulates transcription, DNA replication, and DNA damage response and repair, ensuring the structural integrity of the genome. Deletion of BRE1 or LGE1 also results in whole chromosome instability. We discovered a novel role for Bre1, Lge1 and H2Bub1 in chromosome segregation and sister chromatid cohesion. Bre1's function in G1 and S phases con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This modification also affects centromere integrity and accurate chromosome segregation. It has been shown that the decrease in RNF20 level results in H2B-K119ub1 deficiency in this region, which in turn causes heterochromatin formation, thereby reducing the transcription of the centromeric DNA sequence and resulting in an abnormal chromosome segregation in human and S. pombe (Lindner, 1893) cells (Sadeghi et al 2014, Zhang et al 2017.…”
Section: Epigenetic Regulation Of Centromeres and Pericentromeresmentioning
confidence: 99%
“…This modification also affects centromere integrity and accurate chromosome segregation. It has been shown that the decrease in RNF20 level results in H2B-K119ub1 deficiency in this region, which in turn causes heterochromatin formation, thereby reducing the transcription of the centromeric DNA sequence and resulting in an abnormal chromosome segregation in human and S. pombe (Lindner, 1893) cells (Sadeghi et al 2014, Zhang et al 2017.…”
Section: Epigenetic Regulation Of Centromeres and Pericentromeresmentioning
confidence: 99%